Optimization of type 3 protein secretion in enteropathogenic Escherichia coli. Issue 14 (24th May 2018) - Yuan, Biao; Economou, Anastassios; Karamanou, Spyridoula
Abstract: The type 3 secretion system (T3SS) is a protein export pathway common to Gram-negative pathogens. It comprises a trans-envelope syringe, the injectisome, with a cytoplasm-facing translocase channel. In enteropathogenic Escherichia coli, exported substrates are chaperone-delivered to the major translocase component, EscV, and cross the membrane in strict hierarchical manner, e.g. first 'translocators', then 'effectors'. The in vitro dissection of the T3SS and the determination of its structure are hampered by the low numbers of the injectisomes per cell. We have now defined an optimal M9 minimal medium and established that the per transcriptional regulator enhances the number of filamented cells, the number of injectisomes per cell and the secretion of T3S substrates. Our findings provide a valuable tool for further biochemical and biophysical analysis of the T3SS and suggest that additional improvement to maximize injectisome production is possible in future efforts. Abstract : Optimized type 3 injectisome production is presented to facilitate structural/biochemical dissection